PENATAAN MEKANISME PEMBERIAN GRASI BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Dwi Murniati; Mexsasai Indra; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
A country was born to provide welfare and justice with a regular system to its people, so that each country has a constitution. The constitution of Indonesia is The 1945 Constitution of the Republic of Indonesia (1945 Constitution) which has been amended four times. In article 14 paragraph 1 of The 1945 Constitution of The Republic of Indonesia regulates that the President has the right to grant clemency by taking into account the considerations of the Supreme Court. Clemency is forgiveness in the form of changes, mitigation, reduction or elimination of the implementation of the decision to the convict given by the president. The process of granting clemency in Indonesia is more fully regulated in Law Number 22 Year 2002 Concerning Clemency that has been changed by Law Number 5 Year 2010. Although the process of granting clemency has been regulated in laws, granting clemency issued by the President with a Presidential Decree still causes polemic in the community. There are people and some parties who feel that the clemency issued by the President is not consistent with other government policies and a clemency is often accompanied by unclear reasons. Such as clemency issued for convicted of narcotics, convicted of corruption, and others. So this study aims to determine the mechanism for granting clemency in Indonesia, and the ideal concept of granting clemency in Indonesia.The type of this research can be classified as a type of normative legal research, which clearly illustrates the concept of granting clemency and philosophical clemency if it is associated with the theory of law, justice and legal reform. Data sources used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques in this study were library research methods, after the data were collected then analyzed to make a conclusions.From the results of this study there are two main things that can be concluded. First, the concept of granting clemency in Indonesia and its problems. Second, this research will provide a better ideal concept in the process of granting clemency in Indonesia. The researcher's suggestion are, first the case restrictions that can be granted clemency. Second, a constitutional convention to regularly provide information relating to clemency with a press conference. Third, make the Presidential decree as a state administration decision.Keywords: Granting Clemency - Presidential Power - Justice